Estimating retinal vessel diameter change from the vessel cross-section - Che Azemin, Mohd Zulfaezal; Kumar, Dinesh Kant (2011)
We have developed a methodology to estimate small change in the retinal vessel diameter. This technique does not rely on the segmentation of the vessel which is prone to error when the fitted profile does not exactly represent the expected model. Using the newly proposed method, we have identified an inverse linear relationship (p<0.0001, r 2 = 0.965) between the proposed technique with the narrowing of the simulated vessels. The immediate application of this technique is in the caliber change estimation of the time-series retinal vessels, gated with the electrocardiogram.